Association between GRN rs5848 Polymorphism and Parkinson′s Disease in Taiwanese Population - Chang, Kuo-Hsuan (Public Library of Science, 2013)
A single nucleotide polymorphism GRN rs5848 (3′UTR+78 C>T) was reported to alter the risk for frontotemporal lobar degeneration. Herein, we investigated the effect of GRN rs5848 on the risk of Parkinson’s disease (PD) by genotyping 573 Taiwanese patients with PD and 490 age-matched control subjects. Compared to subjects with CC genotype, those with TT genotype had a 1.58-fold increased risk of PD (95% CI: 1.77∼2.34, P = 0.021). PD patients demonstrate a higher frequency of T allele (37.2%) than controls (32.2%; odds ratio [OR] = 1.24, 95% CI: 1.04∼1.49, P = 0.017). This susceptibility was particularly observed in female subjects, in which TT genotype had a 2.16-fold increased risk of PD as compared with controls(95% CI: 1.24∼3.78, P = 0.006). The frequency of T allele (39.3%) in female PD patients was higher than in female control subjects (31.1%; OR = 1.43, CI: 1.11∼1.87, P = 0.007). No association was observed between GRN rs5848 and susceptibility in male subjects. These findings show that the GRN rs5848 TT genotype and T allele are risk factors for female Taiwanese patients with PD.